Performance assessment of HC-290 as a drop-in substitute to HCFC-22 in a window air conditioner - Devotta, S; Padalkar, AS; Sane, NK (International Journal of Refrigeration - Revue Internationale Du Froid, 2005)
As per the Montreal Protocol, CFCs and HCFCs are being phased out. HCFC-22 is used in window air conditioners. This paper presents the experimental performance study of a window air conditioner with propane (HC-290), a natural refrigerant, as a drop-in substitute to HCFC-22. Experimental results showed that HC-290 had 6.6% lower cooling capacity for the lower operating conditions and 9.7% lower for the higher operating conditions with respect to HCFC-22. The coefficient of performance for HC290 was 7.9% higher for the lower operating conditions and 2.8% higher for the higher operating conditions. The energy consumption of the unit with HC-290 was lower in the range 12.4-13.5% than HCFC-22. The discharge pressures for HC-290 were lower in the range 13.7-18.2% than HCFC-22. For HC-290, the pressure drop was lower than HCFC-22 in both heat exchangers. This paper also presents simulation results for the heat exchangers of an HCFC-22 window air conditioner with HC-290 as a drop-in substitute. The simulation has been carried out using EVAP-COND, a heat exchanger model developed by NIST [National Institute of Standards and Technology. EVAP-COND: simulation models for finned-tube heat exchangers, Maryland, USA (2003). http://www2.bfrl.nist.gov/software/evap-cond/ [18]]. The simulated evaporator capacities are within +/- 4% of the experimentally measured cooling capacities for both refrigerants. Simulation results for HC-290 and HCFC-22 are compared. The exit temperatures of HC-290 are lower by 0.3-1.2 degrees C in the condenser and are higher by 2.1-2.4 degrees C in the evaporator than HCFC-22. Evaporating pressures of HC-290 are lower by 2.1-3.3% as compared to HCFC-22. The pressure drops of HC-290 are lower in both the evaporator and the condenser as compared to HCFC-22. The outlet temperatures of air for HCFC-22 and HC-290 in both heat exchangers are nearly the same. (c) 2005 Elsevier Ltd and IIR. All rights reserved.
Keywords: air conditioner; COP; Evaporator; experiment; performance; propane; R-22; simulation; window

Energy optimization in integrated pulp and paper mills with recourse to environmental benefits - Pharande, V. A.; Asthana, S. R.; Saini, D. R.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2011)
This study focuses on energy optimization in evaporator and digester of integrated pulp and paper mills in India, and recommends application of 7 effects/plates evaporator in place of 5 effects/plates normally used. Steam economy resulting from this modification is definitely more than 7. Pinch technology is found suitable for optimization of controlled parameters in the digester. Using recommendations, total energy savings was observed in West Coast Paper Mill (11.74%) and Star Paper Mill (12.97%). Environmental benefits that will accrue in terms of reductions in emissions are: SPM, 46464-48664 TPA; SO(2), 1045 kg/annum; H(2)S, 55,020 kg/annum; and CO(2), 13612 TPA.
Keywords: Air emissions; Digester; Evaporator; Pinch technology; Steam economy